Open Government Partnership Local Action Plan to Strengthen Governance in Banggai Regency - Hadmar, Ahmad Muhardin; Suranto, Suranto; Purwaningsih, Titin; Nur, Utami (Universitas Medan Area, 2024)
his study explores the Open Government Partnership Local Action Plan (RAD) and its contribution to strengthening governance, focusing on maternal health services in Banggai District. The research employs a qualitative, descriptive approach to analyze three key aspects: action planning, implementation, and evaluation. Findings reveal that the RAD program plays a pivotal role in addressing maternal health challenges, particularly in response to a significant rise in maternal mortality rates. One innovative initiative under the RAD program is Ambulance Dering, which transitioned maternal health services from offline to online through the DraivCare application. This application has introduced transparency, inclusiveness, and digital innovation in service delivery. However, the app’s limited adoption, evident from minimal downloads, indicates the need for enhanced socialization and outreach to increase community utilization. In evaluating the program, five governance principles were examined: transparency, participation, innovation, accountability, and inclusiveness. While the DraivCare application has improved openness and inclusiveness, challenges persist in fostering stronger accountability and active community participation. The study highlights the importance of strategic communication, effective program promotion, and active public involvement to optimize the impact of RAD's governance. Further development of the DraivCare application is recommended to improve its accessibility and functionality, ensuring better outcomes for maternal health services and governance in Banggai District.